Evaluation of the practice of dose‐rounding in paediatrics. (29th May 2019) - Rashed, Asia N.; Tomlin, Stephen; Arenas‐López, Sara; Cavell, Gillian; Whittlesea, Cate
Abstract: Objectives: To investigate the rounding of prescribed drug doses for paediatric administration. Methods: A cross‐sectional medication chart review was conducted at a UK paediatric hospital. Proposed administration dose volumes were calculated for prescribed doses using available manufactured liquids measured with oral and intravenous syringes. Resulting percentage deviations in doses administered were calculated. Results: Of 2031 doses observed, 524 (25.8%) required rounding. The majority of which were for children aged 1–12 months. Twenty‐seven rounded doses deviated from the prescribed dose by more than 10%. Conclusion: This study highlights the impact of dose‐rounding in paediatrics and the need for standardisation.